Mismatch Repair (MMR) protein expression in liver tissue and cancer: A study utilizing Human Protein Atlas Data - Üner, Meral (Acta Medica, 2026)
Objective: Alterations in mismatch repair (MMR) protein expression have been reported in liver cancers, including hepatocellular carcinoma and cholangiocarcinoma. Loss or reduced expression of MMR proteins is commonly associated with microsatellite instability (MSI), which has important prognostic and therapeutic implications. Immunohistochemistry represents a cost-effective and reliable method for detecting deficient MMR (dMMR). However, due to potential technical pitfalls and variable staining patterns, careful interpretation of MMR immunostaining is required. Materials and Methods: In this study, virtual slides of tumor microarray cores from 35 patients were re-evaluated. The cases were stained with different antibody clones targeting MLH1, PMS2, MSH2, and MSH6. Based on the percentage of nuclear staining, immunohistochemical expression patterns were categorized as: (1) total expression loss (<25% nuclear staining), (2) focal expression loss (25-75% nuclear staining), and (3) intact expression (>75% nuclear staining). Results: Among 35 cases (21 hepatocellular carcinomas and 14 cholangiocarcinomas), clone-dependent variability in MMR immunohistochemistry performance was observed. Using the most effective antibody clones, potential dMMR patterns in hepatocellular carcinoma were identified in 25% of cases for MLH1, 50% for MSH2, and 50% for MSH6. In contrast, no dMMR-like pattern was observed in cholangiocarcinoma for any MMR protein. PMS2 (single available clone, CAB010235) demonstrated minimal expression in normal liver tissue and variable staining in tumors, suggesting technical limitations rather than true biological loss. These findings indicate that suboptimal antibody clones may artificially increase the apparent dMMR rate. Conclusion: This study evaluated MMR protein expression patterns in hepatocellular carcinoma and cholangiocarcinoma using data from the Human Protein Atlas, an open-access resource. Although immunohistochemistry remains a cost-effective and reliable method, factors such as fixation quality, antibody clone sensitivity, and careful evaluation of internal controls must be considered. Appropriate antibody clone selection is therefore essential for accurate interpretation of MMR immunostaining.